KAJIAN LAJU PERTUMBUHAN NILAI PAJAK RESTORAN DI BAPENDA KOTA SURABAYA - wika kwana suci; Oryza Tannar (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
The growth of restaurant tax revenues at BAPENDA Surabaya City during the period 2022 to 2024 has not been able to reach the set target. The study was conducted using a qualitative approach and case study method, using data obtained through structured interviews with one of BAPENDA's employees and tax realization reports. Within a period of three years, the average growth rate only reached 15.66%, still far below the minimum success standard of 30%. 2023 showed an increase of 21.43%, but in 2024 there was a sharp decline of 9.89%, reflecting instability in the restaurant tax management process. This condition shows that there is no continuity in the collection strategy that can drive consistent growth. Therefore, a comprehensive evaluation of the existing collection system is needed. Strengthening the use of information technology, updating taxpayer data periodically, and intensifying regulatory counseling to business actors are strategic steps to increase the effectiveness of restaurant tax revenues in the future.